Involvement in the Labor Force and the Likelihood of Marital Violence against Women (International Journal of Innovative Research in Engineering & Management, 2021)
Working has enormous implications for understanding  women's risks of marital violence since it plays such an  important role in forming gender expression as well as gender  relations. By examining employment as a symbolism, instead  of solely economic resource, this research investigates the link  between labor market participation and the risk of spousal  violence against women. We start with such a latent class  analysis, which shows qualitatively diverse patterns of  domestic violence. The next step is to look at the direct and  indirect effects of employment on women's risks of  experiencing spousal abuse. The influence of a woman's career  on her risks of domestic and family violence is mediated by her  spouse's professional level, according to our results. To a  certain extent, these results reflect men' efforts to exert control  over their women partners.
Keywords: Employment; Marital Abuse; Marital Violence; Relationships; Socioeconomic